Multi-Tracer PET-Guided Therapy Selection and Theranostics in Radioiodine-Refractory Thyroid Cancer Patient Unsuitable for Tyrosine Kinase Inhibitor Therapy - Saju, Austin; Sonavane, Sunita; Basu, Sandip (World Journal of Nuclear Medicine, 2025)
Radioactive iodine refractory (RAIR) thyroid cancer and thyroglobulin elevated negative iodine scintigraphy constitute a fraction of thyroid cancer patients with poorer prognosis as opposed to radioiodine concentrating disease. Although not a rare condition and with several treatment options already explored, the selection of an optimal therapy that balances effective disease stabilization, symptom palliation, life prolongation, and minimal side effects remains essential. The use of multi-tracer positron emission tomography (PET) shows potential for radionuclide therapy selection in RAIR thyroid cancer. In this case report, multi-tracer PET imaging was employed to assess the feasibility of available theranostic options. While [68Ga]Ga-DOTATATE PET/computed tomography (CT) showed low-level somatostatin receptor expression, [68Ga]Ga-prostate specific membrane antigen (PSMA)-11 PET/CT revealed moderate and concordant PSMA expression across all lesions observed on [18F]F-FDG PET/CT, justifying [177Lu]Lu-PSMA-617 therapy in this patient.
Keywords: radioiodine-refractory thyroid cancer; multi-tracer PET/CT; theranostics; targeted radionuclide therapy; molecular imaging; PET-guided treatment planning